2011
DOI: 10.1021/jp109451d
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and Microscale Rheological Properties of Poly(vinyl alcohol) Aqueous Solutions

Abstract: Electric conductivity measurements indicated that microviscosities of poly(vinyl alcohol), PVA, solutions [up to 10% (w/w)] are comparable to that of pure water (contrary to Walden's rule), but are different (25%) from those determined from diffusion-controlled reaction measurements that coincide with the values obtained using pure water. Energies of activation of fluidity of PVA solutions are found to increase with PVA concentration, whereas those of the diffusion-controlled reactions are independent of PVA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
5
17
0
Order By: Relevance
“…This behavior agrees with previous reports highlighting the fact that macroviscosity does not always correlates with the microviscosity (i.e., resistance of the medium to the diffusion of small molecules) [53]. Indeed, it has been shown that the cross-linking of a polymer may lead to a rapid rise in macroviscosty while the movement of small molecules through the network is not altered since they move through the so called "interconnected water pools" among the chains [54].…”
Section: Formulationsupporting
confidence: 92%
“…This behavior agrees with previous reports highlighting the fact that macroviscosity does not always correlates with the microviscosity (i.e., resistance of the medium to the diffusion of small molecules) [53]. Indeed, it has been shown that the cross-linking of a polymer may lead to a rapid rise in macroviscosty while the movement of small molecules through the network is not altered since they move through the so called "interconnected water pools" among the chains [54].…”
Section: Formulationsupporting
confidence: 92%
“…4144 A study showed that the diffusion of “small” molecules or ions through the solutions of this polymer was not affected by the presence of “large” polymer molecules. 40…”
Section: Introductionmentioning
confidence: 99%
“…16,17,[37][38][39] Polyvinyl alcohol (PVA) is a hydrophilic polymer with hydrated molecules when dissolved in water. 40 It has been widely used for drug delivery systems, wound dressing, and other medical prosthetics because of its biocompatible properties. [41][42][43][44] A study showed that the diffusion of "small" molecules or ions through the solutions of this polymer was not affected by the presence of "large" polymer molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work expands on our previous work with simple aqueous polymer solutions in which we showed that (despite high macroviscosity) the physiochemical properties of water in poly(vinyl alcohol) aqueous solutions (up to 10% (w/w)) were the same as those of pure water. 12 Here using diffusion-controlled reactions and electric conductivity involving small reactants and ions, we investigated the mobility of molecules and ions solubilized within the thick fraction of egg white to characterize its microscale rheological properties. Differential scanning calorimetry (DSC) was used to gain further information about the amount of bound water in the hydrogel as well as water pool and channel sizes within the thick fraction.…”
mentioning
confidence: 99%